Law Enforcement Of Digital Asset Confiscation In Money Laundering Crimes - Tb. Soenmandjaja SD; Hono Sejati; Lamijan Lamijan (Al-Makki Publisher, 2024)
Money laundering is a serious crime that harms the interests of society, causes economic instability in a country, and is more dangerous than corruption because tracking the flow of money from money laundering will be more difficult. Due to this complexity, asset forfeiture becomes crucial because the approach method used is known as